Effort for Developing Excellent Human Resources in the Hospitality Industry - Mahsun, Mahsun; Rizal, Rizal Kurniansah (Journal of Asian Multicultural Research for Economy and Management Study, 2021)
The hospitality industry is an industry that prioritizes service for its guests, to provide the best service, of course, it requires superior, competent, and professional human resources in their field. To get HR with these criteria, of course, there are various efforts that can be made by every hotel company. The purpose of this study is to describe efforts to develop superior human resources in the hospitality industry, through this development it can provide an overview for hotel leaders in developing their human resources so that competent human resources are created in their fields who are able to provide the best service to guests. This type of research is qualitative research with the method of Data collection used is a literature study. Based on the results of the discussions that have been described, in an effort to build superior human resources in the hospitality industry, companies can make various efforts, including conducting recruitment and selection properly and fairly, providing opportunities for every employee to carry out education and training activities, providing opportunities for Career development for each employee, employees are able to cooperate with each other within the company, create a good and conducive work environment, improve technology capabilities for each employee, reward employees who excel and contribute positively to the progress of the company.